2019
DOI: 10.1021/acs.bioconjchem.8b00916
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Biocompatible Monodispersion of C60 in Water by Peptides

Abstract: The lack of solubility in water and the formation of aggregates hamper many opportunities for technological exploitation of C60. Here, different peptides were designed and synthesized with the aim of monomolecular dispersion of C60 in water. Phenylalanines were used as recognizing moieties, able to interact with C60 through π–π stacking, while a varying number of glycines were used as spacers, to connect the two terminal phenylalanines. The best performance in the dispersion of C60 was obtained with the FGGGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“…If we consider the extended π-system of the fullerene, it is not surprising that aromatic amino acids such as tryptophan, tyrosine, phenylalanine, and histidine interacted the most with it ( Figure 3 ) [ 20 , 24 , 33 , 34 , 35 , 39 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. In particular, Trp exhibited the largest value of binding energy among the twenty proteinogenic amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If we consider the extended π-system of the fullerene, it is not surprising that aromatic amino acids such as tryptophan, tyrosine, phenylalanine, and histidine interacted the most with it ( Figure 3 ) [ 20 , 24 , 33 , 34 , 35 , 39 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. In particular, Trp exhibited the largest value of binding energy among the twenty proteinogenic amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Supramolecular approaches can preserve these properties [ 19 ]. Recently, it was demonstrated that it is possible to use peptides [ 20 ] and proteins [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] as supramolecular hosts for the non-covalent dispersion of fullerenes [ 21 ]. Different proteins, such as albumins [ 22 , 23 ], lysozyme [ 23 , 24 , 25 , 26 ], pepsin [ 27 ], trypsin [ 27 ], or natural protein surfactants [ 28 ] were used for the mono-molecular dispersion of pristine fullerenes in a physiological environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 45–47 ] Proteins and peptides can be used as biocompatible hosts for fullerenes, allowing the dispersion of fullerenes as single molecules in physiological environments to prevent aggregation phenomena. [ 48–53 ] In particular, lysozyme binds and disperses C 60 in water, and the resulting C 60 @lysozyme complex is still photoactive, generating significant quantities of ROS upon visible light irradiation, while remaining biocompatible in dark conditions. [ 48 ] It was shown that irradiation of C 60 @lysozyme with visible light significantly reduced the viability of HeLa cells in vitro, making it a candidate for PDT.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction with proteins may affect the photophysical properties of photosensitizers, [ 56 , 57 , 58 , 59 , 60 , 61 ] so we evaluated the BGNP performances in a physiological-like conditions, investigating the possible effects of the biomolecular corona during laser the irradiation/heating process [ 44 ]. We repeated the irradiation experiment for the FBS-dispersed BGNPs, using the highest concentration of BGNPs (0.25 mM Au 0 BGNPs).…”
Section: Resultsmentioning
confidence: 99%